Advancing Green Marketing in Southeast Asia’s Cosmetics Industry: A Systematic Literature Review of Trends, Challenges, and Opportunities - Zelika Nidya Damarani; Rista Nurdianasari; Shabira Maharani (Transpublika Publisher, 2025)
The cosmetics sector in Southeast Asia is undergoing swift changes, spurred by a global surge in environmental consciousness and the embrace of sustainable business practices. This research employs a Systematic Literature Review (SLR) to explore the development, opportunities, and obstacles of green marketing in the region’s cosmetics industry. Using the PRISMA framework, 80 peer-reviewed articles published from 2020 to 2025 were examined across six thematic areas: consumer behavior, corporate green strategies, technological innovation, institutional and financial support, socio-cultural and regulatory context, and sustainable operational practices. The study’s findings indicate that environmental awareness, health consciousness, and brand authenticity are the most significant predictors of purchasing behavior for green cosmetics, while price sensitivity and a lack of understanding of eco-labels remain major challenges. The incorporation of corporate social responsibility (CSR), digital innovation, and eco-design boosts consumer trust and brand differentiation, making green marketing both a competitive strategy and a driver of sustainability. However, regional differences, inconsistent regulations, and weak enforcement hinder the widespread adoption of sustainable practices. The review highlights research gaps, such as the need for cross-country comparative studies, mechanisms to detect greenwashing, and technology-enabled transparency frameworks. Overall, green marketing in Southeast Asia’s cosmetics industry is showing increasing maturity and strategic alignment with the United Nations Sustainable Development Goals (SDGs), particularly Responsible Consumption and Production (SDG 12) and Climate Action (SDG 13), emphasizing its crucial role in promoting sustainable economic growth and ethical consumerism.